Recent Periodicals: Local History, Family and Community History, Cultural Heritage, Folk Studies, Anthropology - A Review (2016) - R., Vladova (SCS Consulting Ltd., 2018)
An annual bibliography of papers in the field of local history, family and community history, cultural heritage, folk studies and anthropology, published in 2016, is collected. The inspected journals are: Bulgarian Journal of Science and Education Policy, Chemistry: Bulgarian Journal of Science Education, Current Anthropology, Family and Community History, Folklore, History and Memory, Journal of Family History, Journal of Folklore Research, Past & Present, Winterthur Portfolio. Many of those journals are available at us under subscription.